2022
DOI: 10.1097/j.jcro.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial wound healing after Descemet tear with a rho kinase inhibitor

Abstract: Introduction:To the authors’ knowledge, this is the first report of Descemet tear postcataract surgery that was successfully treated with ripasudil hydrochloride hydrate.Patient and Clinical Findings:An 85-year-old pseudophakic man presented with blurry vision and mild photophobia in the left eye. Slitlamp biomicroscopy showed moderate corneal edema and a central Descemet tear from cataract surgery 7 years earlier.Diagnosis, Intervention, and Outcomes:The patient was treated for 1 month with prednisolone aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Cataract or anterior segment surgeries are known to be associated with a risk of postoperative corneal oedema due to endothelial cell damage. Studies have shown that administering ripasudil in the post-operative period has a protective effect on endothelial cell density [38], and may improve visual recovery after complicated procedures [39,40]. In both Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) and penetrating keratoplasty corneal grafts that failed to clear with conservative management, vision can be rescued with ripasudil therapy [41].…”
Section: Ripasudil In Corneal Diseasesmentioning
confidence: 99%
“…Cataract or anterior segment surgeries are known to be associated with a risk of postoperative corneal oedema due to endothelial cell damage. Studies have shown that administering ripasudil in the post-operative period has a protective effect on endothelial cell density [38], and may improve visual recovery after complicated procedures [39,40]. In both Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) and penetrating keratoplasty corneal grafts that failed to clear with conservative management, vision can be rescued with ripasudil therapy [41].…”
Section: Ripasudil In Corneal Diseasesmentioning
confidence: 99%